2016
DOI: 10.1038/ncomms10835
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic supramolecular solid catalyst boosts organic reactions in water

Abstract: Coordination polymers and metal-organic frameworks are appealing as synthetic hosts for mediating chemical reactions. Here we report the preparation of a mesoscopic metal-organic structure based on single-layer assembly of aluminium chains and organic alkylaryl spacers. The material markedly accelerates condensation reactions in water in the absence of acid or base catalyst, as well as organocatalytic Michael-type reactions that also show superior enantioselectivity when comparing with the host-free transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 52 publications
0
60
0
Order By: Relevance
“…MOFs have been explored for a broad range of catalytic transformations. Reported examples are condensation, ring opening, cycloaddition, N ‐alkylation, isomerization, hydrogenation, oxidation, and carbene reactions. MOF‐based materials are suitable catalysts for the production of certain fine chemicals .…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have been explored for a broad range of catalytic transformations. Reported examples are condensation, ring opening, cycloaddition, N ‐alkylation, isomerization, hydrogenation, oxidation, and carbene reactions. MOF‐based materials are suitable catalysts for the production of certain fine chemicals .…”
Section: Introductionmentioning
confidence: 99%
“…115 This reaction has been widely studied and different catalysts such as [Amb]L-prolinate, 116 tetrabutylammonium bromide (TBAB), 117 boron nitride supported iron oxide (BN@Fe3O4), 118 AI-ITQ-HB, 119 [bmim]OH, 120 Fe3O4, 121 carbon nanotube (CNT), 122 NaOAc, 123 CuFe2O4 nanoparticles 124 and trisodium citrate dihydrate 125 were used in this reaction.…”
Section: Scheme 67mentioning
confidence: 99%
“…Organic synthesis reactions on water at the organic-liquid water interface were studied by Butler et al [27]. García-García et al [28] have reported the preparation of a mesoscopic metal-organic structure based on single-layer assembly of aluminium chains and organic alkylaryl spacers. The material markedly accelerates condensation reactions in water in the absence of acid or base catalyst, as well as organocatalytic Michael-type reactions that also show superior enantioselectivity when comparing with the host-free transformation [28].…”
Section: Synthesis Of Substituted Fused Thiazole Derivatives [25]mentioning
confidence: 99%